Modeling of the high-resolution optical-coherence diagnostics of bi-refringent biological tissues - Angelsky, O. V.; Bekshaev, A. Ya.; Zenkova, C. Yu.; Ivanskyi, D. I.; Zheng, J.; Chumak, M. M. (Frontiers in Physics, 2023)
We present a computer model of the polarization-sensitive interference diagnostics of the birefringent biological media, with a particular example of the lamella of eye cornea. The diagnostic procedure employs the modified Mach -Zehnder interferometer with controllable phase retardation of the reference wave, separate observation of the orthogonal linearly-polarized interference signals, and evaluation of the phases and amplitudes of their variable (AC) components. The data obtained permit to determine the mean refractive index as well as the difference between the extraordinary and ordinary refractive indices, which, in turn, indicates the optical axis and the collagen fibers' orientation in the lamella. The modelled procedure enables the sample structure diagnostics with the longitudinal and lateral resolution 100 nm and 1.8 µm, correspondingly. In particular, it permits a reliable detection and quantitative characterization of a thin (<100 nm) near-surface layer where the mean refractive index differs by less than 1% from that in the main volume (due to the different orientation of the collagen fibers). The diagnostic approach, developed in the paper, can be useful in various problems of structure characterization of optically-anisotropic biological tissues.